The Gibraltar slab dynamics and its influence on past and present-day Alboran domain deformation: Insights from thermo-mechanical numerical modelling - Gea, Pedro J.; Negredo, Ana M.; Mancilla, Flor de Lis (Frontiers in Earth Science, 2023)
The origin and tectonic evolution of the Gibraltar Arc system is the result of a complex geodynamic evolution involving the convergence of the Eurasian and African plates and the dynamic impact of the Gibraltar slab. Although geologic and geophysical data collected in the last few years have increased our knowledge of the Gibraltar Arc region, it is still unclear which are the mechanical links between the Gibraltar slab and the past deformation of the overriding Alboran lithosphere, as well as to which degree this subduction system is presently active. In this study, we use 2D numerical modelling to investigate the impact of the Gibraltar slab dynamics on the deformation of the overriding Alboran lithosphere. Our model simulates a WE generic vertical section at an approximate latitude of 36◦N and considers an initial setup at about Burdigalian times (∼20 Ma), when the subduction front position is relatively well constrained by recent tectonic reconstructions. Our modelling shows a switch in the overriding plate (OP) stress state from extensional stresses during the slab rollback to compressional stresses near the trench when the rollback velocity decreases, caused by the change in slab-induced mantle flow. We also find that much of the crustal and lithospheric deformation occur during fast slab rollback and OP extension in the first 10 Myr of evolution, while after that only moderate deformation associated with subduction is predicted. Finally, we find that despite the subduction rollback ceases, the ongoing motion of the deeper portion of the slab induces a mantle flow that causes some amount of west-directed basal drag of the Alboran lithosphere. This basal drag generates interplate compresional stresses compatible with the distribution of intermediate-depth earthquakes in western Alboran.